Metaphorical Expressions in Ariana Grande's Eternal Sunshine Album - Ade Putri Luthfiah; Novi Wulandari; Ainul Yaqin (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
This article examines metaphorical expressions in selected song lyrics from Ariana Grande's Eternal Sunshine album. Although the topic is related to a broader thesis on the album, this manuscript is written as an independent journal article by narrowing the discussion to conceptual metaphor mappings and their emotional functions in the lyrics. The study applies a descriptive qualitative method. The data are taken from five selected songs, namely Eternal Sunshine, Don't Wanna Break Up Again, We Can't Be Friends (Wait for Your Love), True Story, and Imperfect for You. The analysis is based on Lakoff and Johnson's Conceptual Metaphor Theory, which classifies metaphor into structural, ontological, and orientational types. The findings reveal fifteen metaphorical patterns. Ontological metaphor is the most dominant type because the lyrics frequently represent abstract feelings as concrete entities, such as objects, wounds, burdens, traces, and spaces. Structural metaphor frames romantic relationships as cycles, stories, struggles, performances, and waiting, while orientational metaphor represents emotional separation as distance and vulnerability as openness. The article concludes that metaphor in popular song lyrics functions not merely as an aesthetic ornament, but also as a cognitive and literary device that organizes emotional experiences of heartbreak, memory, distance, imperfection, and healing.